Wild boar populations up, numbers of hunters down? A review of trends and implications for Europe. Issue 4 (29th January 2015) - Massei, Giovanna; Kindberg, Jonas; Licoppe, Alain; Gačić, Dragan; Šprem, Nikica; Kamler, Jiří; Baubet, Eric; Hohmann, Ulf; Monaco, Andrea; Ozoliņš, Janis; Cellina, Sandra; Podgórski, Tomasz; et al.
Abstract Across Europe, wild boar numbers increased in the 1960s–1970s but stabilised in the 1980s; recent evidence suggests that the numbers and impact of wild boar has grown steadily since the 1980s. As hunting is the main cause of mortality for this species, we reviewed wild boar hunting bags and hunter population trends in 18 European countries from 1982 to 2012. Hunting statistics and numbers of hunters were used as indicators of animal numbers and hunting pressure. The results confirmed that wild boar increased consistently throughout Europe, while the number of hunters remained relatively stable or declined in most countries. We conclude that recreational hunting is insufficient to limit wild boar population growth and that the relative impact of hunting on wild boar mortality had decreased. Other factors, such as mild winters, reforestation, intensification of crop production, supplementary feeding and compensatory population responses of wild boar to hunting pressure might also explain population growth. As populations continue to grow, more human–wild boar conflicts are expected unless this trend is reversed. New interdisciplinary approaches are urgently required to mitigate human–wild boar conflicts, which are otherwise destined to grow further. © 2014 Crown copyright. Pest Management Science © 2014 Society of Chemical Industry